Qualitative Research in the Post-Modern Era : Critical Approaches and Selected Methodologies - White, Robert E., 1948-, author 645784; Cooper, Karyn, 1957-, author 645785 (Cham, Switzerland : Springer, 2022)
This volume describes and discusses some of the intricacies associated with qualitative research in this post-modern era. It is the second of a two-volume set. It strives to define terms, identifies paradigms, methodologies and approaches that are applicable to noviceand expert researchers alike. The book pays special attention to the biographies of those individuals who havehelped to shape and develop these methodologies or research designs. In addition, consideration is given to historical and political underpinnings that relate to the development of qualitative research methodologies. Each research design is described in detail and the similarities and differences among them are explored. This volume makes use of a contextual approach to research and features interviews with scholars who have assisted in developing such methodologies. Of interest are numerous features such as questions for further study and annotated bibliographies that extend the scope of each of the methodologies described.